∫ 0 ∞ x 3 x cos x − sin x d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Contour Integration
Define I ( ε , R ) = ∫ ε R x 3 x cos x − sin x d x and note that we want to find I : = ε → 0 + lim R → ∞ lim I ( ε , R ) .
The function x 3 x cos x − sin x is even, so we have 2 I ( ε , R ) = ∫ − R − ε x 3 x cos x − sin x d x + ∫ ε R x 3 x cos x − sin x d x , and x 3 ( i x − 1 ) e i x = x 3 − cos x − x sin x + i ⋅ x 3 x cos x − sin x so that for real values of x , we have Im ( x 3 ( i x − 1 ) e i x ) = x 3 x cos x − sin x . Using this, we can write 2 I ( ε , R ) = Im ( ∫ − R − ε x 3 ( i x − 1 ) e i x d x + ∫ ε R x 3 ( i x − 1 ) e i x d x ) .
Using the expression on the right-side to direct us, we consider the contour integral ∫ γ z 3 ( i z − 1 ) e i z d z where γ = γ − ∪ ( − γ ε ) ∪ γ + ∪ ( − γ R ) has four pieces defined by γ − γ + γ ε γ R = Line segment from z = − R to z = − ε = Line segment from z = ε to z = R = Upper half of the circle ∣ z ∣ = ε , traversed counterclockwise = Upper half of the circle ∣ z ∣ = R , traversed clockwise Since the integrand is analytic everywhere except z = 0 , which lies outside γ , the Cauchy Goursat Theorem tells us that ∫ γ z 3 ( i z − 1 ) e i z d z = 0 , so that ∫ − R − ε x 3 ( i x − 1 ) e i x d x + ∫ ε R x 3 ( i x − 1 ) e i x d x = ∫ γ − ∪ γ + z 3 ( i z − 1 ) e i z d z = ∫ γ ε z 3 ( i z − 1 ) e i z d z + ∫ γ R z 3 ( i z − 1 ) e i z d z ⟹ I = 2 1 ε → 0 + lim R → ∞ lim 2 I ( ε , R ) = 2 1 ε → 0 + lim R → ∞ lim Im ( ∫ γ ε z 3 ( i z − 1 ) e i z d z + ∫ γ R z 3 ( i z − 1 ) e i z d z ) = 2 1 Im ( ( ε → 0 + lim ∫ γ ε z 3 ( i z − 1 ) e i z d z ) + ( R → ∞ lim ∫ γ R z 3 ( i z − 1 ) e i z d z ) )
Therefore, we compute each of these two integrals separately:
Now combining all our results, we find the answer: I = 2 1 Im ( ( ε → 0 + lim ∫ γ ε z 3 ( i z − 1 ) e i z d z ) + ( R → ∞ lim ∫ γ R z 3 ( i z − 1 ) e i z d z ) ) = 2 1 Im ( − 2 π i + 0 ) = − 4 π ≈ − 0 . 7 8 5 3 9 8 1 6 3
Problem Loading...
Note Loading...
Set Loading...
To avoid manipulating singularities, start by considering G t ( u ) = ∫ 0 ∞ x sin u x e − t x d x u ∈ R , t > 0 Then G t ( 0 ) = 0 and G t ′ ( u ) = ∫ 0 ∞ e − t x cos u x d x = 2 1 ∫ 0 ∞ e − t x ( e i u x + e − i u x ) d x = 2 1 ( t − i u 1 + t + i u 1 ) = t 2 + u 2 t and hence G t ( u ) = ∫ 0 u t 2 + v 2 t d v = tan − 1 t u u ∈ R , t > 0 If we now define F t ( u ) = ∫ 0 ∞ x 3 u x cos u x − sin u x e − t x d x u ∈ R , t > 0 then F t ( 0 ) = 0 and F t ′ ( u ) = ∫ 0 ∞ x 3 x cos u x − u x 2 sin u x − x cos u x e − t x d x = − u ∫ 0 ∞ x sin u x e − t x d x = − u G t ( u ) = − u tan − 1 t u so that F t ( u ) = − ∫ 0 u v tan − 1 t v d v u ∈ R , t > 0 Letting t → 0 + gives ∫ 0 ∞ x 3 u x cos u x − sin u x d x = t → 0 + lim F t ( u ) = − 2 1 π ∫ 0 ∞ v d v = − 4 1 π u 2 and hence the desired integral is, putting u = 1 , equal to − 4 1 π . Alternatively, integration by parts enables us to evaluate F t ( u ) explicitly F t ( u ) = − 2 1 u 2 tan − 1 t u + t 2 [ t u − tan − 1 t u ] and we can readily take the limit of this expression as t → 0 + .
Adding the term e − t x ensures that all integrands are Lebesgue-integrable for all t > 0 , which makes the process of differentiation under the integral sign valid. The validity of taking the limit as t → 0 + follows from the Dominated Convergence Theorem.